Urinary total conjugated 3-bromotyrosine, asthma severity, and exacerbation risk - Wang, Zeneng; Xu, Weiling; Comhair, Suzy A. A.; Fu, Xiaoming; Shao, Zhili; Bearden, Rebecca; Zein, Joe G.; Bleecker, Eugene R.; Castro, Mario; Denlinger, Loren C.; Fahy, John V.; Israel, Elliot; et al. (American journal of physiology. Lung cellular and molecular physiology, 2022)
Asthma is an inflammatory disease of the airways characterized by eosinophil recruitment, eosinophil peroxidase release, and protein oxidation through bromination, which following tissue remodeling results in excretion of 3-bromotyrosine. Predicting exacerbations and reducing their frequency is critical for the treatment of severe asthma. In this study, we aimed to investigate whether urinary total conjugated bromotyrosine can discriminate asthma severity and predict asthma exacerbations. We collected urine from participants with severe ( n = 253) and nonsevere ( n = 178) asthma, and the number of adjudicated exacerbations in 1-yr longitudinal follow-up was determined among subjects enrolled in the Severe Asthma Research Program, a large-scale National Institutes of Health (NIH)-funded consortium. Urine glucuronidated bromotyrosine and total conjugated forms were quantified by hydrolysis with either glucuronidase or methanesulfonic acid, respectively, followed by liquid chromatography-tandem mass spectrometry analyses of free 3-bromotyrosine. Blood and sputum eosinophils were also counted. The majority of 3-bromotyrosine in urine was found to exist in conjugated forms, with glucuronidated bromotyrosine representing approximately a third, and free bromotyrosine less than 1% of total conjugated bromotyrosine. Total conjugated bromotyrosine was poorly correlated with blood ( r 2 = 0.038) or sputum eosinophils ( r 2 = 0.0069). Compared with participants with nonsevere asthma, participants with severe asthma had significantly higher urinary total conjugated bromotyrosine levels. Urinary total conjugated bromotyrosine was independently associated with asthma severity, correlated with the number of asthma exacerbations, and served as a predictor of asthma exacerbation risk over 1-yr of follow-up.